2018
DOI: 10.3390/ma12010060
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, Physico-Chemical, and Mechanical Behaviour of Mass Concrete with Hybrid Blends of Bentonite and Fly Ash

Abstract: Mass concrete has been commonly known for its thermal stresses which arise due to the entrapment of hydration temperature susceptible to thermal cracking. The utilization of mineral additives is a promising and widely adopted technique to mitigate such effects. This paper presents the thermal, physico-chemical, mechanical, and morphological behaviour of mass concrete with blends of bentonite (BT) and fly ash (FA). Apart from the rise in temperature due to hydration, the compressive strength, ultrasonic pulse v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Such a massive strength reduction is in accordance with rise in porosities, as well as with the nature of raw material. The minor or major decrease of compressive strength due to the bentonite (or montmorillonite respectively) was observed also by other researchers [8,12,13]. However, from the achieved results and the huge drop of mechanical strengths, it can be assumed, that not even 10% of bentonite acted as pozzolanic material, and its application in this way is not suitable.…”
Section: Mechanical Parametersmentioning
confidence: 72%
“…Such a massive strength reduction is in accordance with rise in porosities, as well as with the nature of raw material. The minor or major decrease of compressive strength due to the bentonite (or montmorillonite respectively) was observed also by other researchers [8,12,13]. However, from the achieved results and the huge drop of mechanical strengths, it can be assumed, that not even 10% of bentonite acted as pozzolanic material, and its application in this way is not suitable.…”
Section: Mechanical Parametersmentioning
confidence: 72%
“…It is one of the widely using pozzolanic materials in construction industry [3]. The performance of fresh and hardened properties of concrete will enhance by incorporation of fly ash in concrete [4]. Fly ash will not be generated once the thermal power plants is permanently shutdown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that fly ash is a potential and versatile adsorbent for wastewater [ 5 , 6 ] and the removal of pollutants, such as dyes from aqueous solutions [ 7 , 8 ]. From a chemical structure point of view, fly ash is aluminosilicate layered [ 9 , 10 ]. Abundant hydrophilic hydroxyls are decorated on its surface, and a large number of exchangeable cations are located between interlayers, which give fly ash excellent dispersibility in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%